Problems and Prospectus of Mushroom Farming in Nepal - Acharya, Krishna Raj; Dhungel , Bashu Dev (Management Dynamics, 2021)
Mushroom farming is popular among farmers worldwide since consumers demand it as a vegetable and rich source of protein. Farming itself has been surrounded by various problems in Nepal, like countries worldwide. Based on primary data, it was revealed that open border was the main problem faced by Nepalese farmers to get reasonable price of mushrooms. 56.7 % of respondents opined that there is a market problem as well as poor technologies in the time of cultivation and harvesting of product. Forty-three percent of the respondents had a market problem but no poor technology. It can be explained as better technology used in the field of production. Total production starts to increase and may not have a market problem. Seventy-five percent of the farmers believed there was no adequate fund or irrigation facility. High cost and middle man problems were felt by 90 percent of farmers. There was a labour problem and a lack of training. Only 20 % have training in this farming. These two variables were statistically significant. P-Value is less than .05 > .002 show their association. 90 % of the farmer has an open border, which is the cause of a decrease in mushroom farming. These variables are statistically significant. P-Value is less than .05 > .03, representing a close relationship between these problems. Eliminating such problems may open the door to more investment, employment and income in the national economy.